Effects of Biological Sex and Stress Exposure on Ventromedial Prefrontal Regulation of Mood-Related Behaviors - Wallace, Tyler; Myers, Brent (Frontiers in Behavioral Neuroscience, 2021)
The ventral portion of the medial prefrontal cortex (vmPFC) regulates mood, sociability, and context-dependent behaviors. Consequently, altered vmPFC activity has been implicated in the biological basis of emotional disorders. Recent methodological advances have greatly enhanced the ability to investigate how specific prefrontal cell populations regulate mood-related behaviors, as well as the impact of long-term stress on vmPFC function. However, emerging preclinical data identify prominent sexual divergence in vmPFC behavioral regulation and stress responsivity. Notably, the rodent infralimbic cortex (IL), a vmPFC subregion critical for anti-depressant action, shows marked functional divergence between males and females. Accordingly, this review examines IL encoding and modulation of mood-related behaviors, including coping style, reward, and sociability, with a focus on sex-based outcomes. We also review how these processes are impacted by prolonged stress exposure. Collectively, the data suggest that chronic stress has sex-specific effects on IL excitatory/inhibitory balance that may account for sex differences in the prevalence and course of mood disorders.